PREDICTING CORPORATE PERFORMANCE FROM ORGANIZATIONAL CULTURE* - Gordon, George G.; DiTomaso, Nancy (Journal of Management Studies, 1992)
ABSTRACTThis article investigates the relationships of culture strength and two substantive cultural values with corporate performance. Culture strength is measured by the consistency of responses to survey items across people and the two cultural values are measured by items on the survey that relate to either adaptability or stability. The data, from management surveys of 11 US insurance companies in 1981, were correlated with asset and premium growth rates from 1982 to 1987. Results indicate that both a strong culture regardless of content and a substantive value placed on adaptability are associated with better performance for two to three subsequent years on both criterion measures. The results support the findings of Denison (1990) that strength of culture is predictive of short‐term performance. The present results, however, suggest a more complex contingency model than that proposed by Denison.